ANALYSIS OF FINANCIAL PLANNING ON THE FINANCIAL STABILITY OF PT. CIPTA INOVASI - Sitti Hafsah (CV. Adiba Aisha Amira, 2026)
This study aims to analyse the impact of financial planning on the financial stability of PT. Cipta Inovasi, an innovative technology company focused on the development of digital products. Using a qualitative and quantitative approach, data was collected through an analysis of the company’s annual financial statements from 2018 to 2022, as well as interviews with the financial management team. The analytical methods included financial ratios such as liquidity, solvency, and profitability ratios, as well as long-term financial planning scenario simulations using a cash flow projection model. The research findings indicate that effective financial planning, including investment risk management and diversification of funding sources, has improved the company’s financial stability by 25% over the observation period, primarily through reduced cash flow volatility and an increase in the solvency ratio from 0.45 to 0.62. However, challenges such as fluctuations in the technology market and reliance on venture capital remain potential risks. The study’s conclusions recommend strengthening data-driven financial planning strategies to maintain long-term stability, with practical implications for similar companies in the innovation sector.